Pengaruh Instagramable, Memorable Tourist Experience dan Destination Image pada Revisit Intention di Pantai Sayang Heulang Kabupaten Garut - Purnama, Alam; Adiatma, Dani; Rukma, Deden Firman Syuyaman (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of instagrammable, memorable tourist experience and destination image on revisit intention to Sayang Heulang Beach in Garut Regency. The research sample consisted of 100 respondents. Data is taken through a questionnaire that has gone through rigorous testing to ensure its validity and reliability. The data analysis technique used is descriptive analysis with SEM PLS 3.0. The research results show that there is a direct effect of the instagramable variables, memorable tourist experience and destination image on revisit intention. This means that interest in revisiting (revisit intention) can be built or influenced by instagrammable photo spots and facilities that support tourist activities so as to provide good memories and a unique destination image.